Eelectrochemical Evaluation of Self-assembled Monolayers of N-Heterocyclic Carbenes on Gold and DFT Studies. Issue 1 (27th January 2021) - Mao, Junwei; Xu, Pengfei; Zhou, Zhenju; Zhou, Yu; Tang, Yongming
Abstract : Three N-heterocyclic carbenes (NHCs) are synthesized and their self-assembled monolayers (SAMs) are built up on gold substrate. Electrochemical impedance spectroscopy (EIS) tests show that the NHC-based SAMs exhibit high stability in 0.1 M HCl solution, and the loss of NHC molecules on gold surface is less than 3% after immersion of 32 h. The unsaturated level of heterocyclic moiety has a negligible effect on the stability of NHC-SAMs, which is attributed to the special bonding mechanism between NHCs and gold atom. Theoretical calculations reveal that the bonding of NHC molecule is dominantly contributed by the interaction of the d orbital of gold atom with the molecular orbitals mainly distributing on carbene carbon atom of NHC, such as HOMO-1 ( σ 1) and HOMO-2 ( π 1), and the σ -type interaction accounts for the main state of bonding in comparison to the π -type one. Those molecular orbitals distributing on heterocyclic moiety nearly take no part in the bonding, and the interaction of isopropyl substituents on N atoms with gold surface is not observed in this study. In addition, it is confirmed that EIS measurement can both sensitively and quantitatively examine the adsorption and desorption of SAMs on gold surface.